2021
DOI: 10.1039/d1nr01859k
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared II laser controlled free radical releasing nanogenerator for synergistic nitric oxide and alkyl radical therapy of breast cancer

Abstract: Recently, alkyl radical has attracted much attention in cancer therapy due to its oxygen-independent generation property. For the first time, alkyl radical and nitric oxide (NO) combined therapy is demonstrated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…N,N-bis(Carboxymethyl)-N,N-dinitroso-p-phenylenediamine (BNN6) is the most commonly used N-nitrosoamine. [158,159] Based on the second approach, Huang et al utilized magnesium silicate-coated upconverting nanoparticles UCNPs@MgSiO 3 based on a yolk-shell structure as a carrier to load the NO precursor BNN6 and anticancer drug DOX Figure 22. [160] UCNPs can convert NIR to UV or visible light, activating the loaded BNN6 to release NO, which avoids the phototoxicity of direct UV light excitation.…”
Section: Light-triggered Releasementioning
confidence: 99%
“…N,N-bis(Carboxymethyl)-N,N-dinitroso-p-phenylenediamine (BNN6) is the most commonly used N-nitrosoamine. [158,159] Based on the second approach, Huang et al utilized magnesium silicate-coated upconverting nanoparticles UCNPs@MgSiO 3 based on a yolk-shell structure as a carrier to load the NO precursor BNN6 and anticancer drug DOX Figure 22. [160] UCNPs can convert NIR to UV or visible light, activating the loaded BNN6 to release NO, which avoids the phototoxicity of direct UV light excitation.…”
Section: Light-triggered Releasementioning
confidence: 99%
“…The synergistic action of NO and alkyl radicals induced the high oxidative stress in mitochondria, which could not only accelerate the release of cytochrome C to cause mitochondrial membrane damage but also significantly down-regulate the Bcl-2 protein to trigger the apoptosis of tumor cells. Animal experiments have shown that mice treated with this strategy can survive for more than 40 days and have a tumor suppression rate of more than 70% (Figure 3C) [78]. Furthermore, Tian et al designed a type of microsphere for the treatment of cold tumors using the photothermal agent IR1061, NO donor SNO and 1-methyl-tryptophan(1-MT).…”
Section: Second Nir (Nir-ii) Photothermal Triggered No Nanomedicinesmentioning
confidence: 99%
“…As a typical free radical initiator, 2,2′-azobis[2-(2-imidazolin-2-yl)propane]-dihydrochloride (AIPH) can generate alkyl radicals at high temperatures. 12 It does so even in the absence of oxygen. The generated free radicals are toxic to cells and will immediately oxidize cell elements or interact with oxygen to produce secondary toxic substances.…”
Section: Introductionmentioning
confidence: 99%
“…The released alkyl radicals can induce apoptosis of cancer cells by increasing oxidative stress, leading to cellular lipid and DNA damage. As a typical free radical initiator, 2,2'-azobis[2-(2-imidazolin-2-yl) propane]-dihydrochloride (AIPH) can generate alkyl radicals at high temperatures 12 . It does so even in the absence of oxygen.…”
Section: Introductionmentioning
confidence: 99%